Traditional and Modern Analysis Performance Indicators: Evidence from New York Stock Exchange - Cahyo Indraswono (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2021)
Assessment of company performance can be done using traditional and modern techniques. Each test carried out has the advantages and disadvantages of the order if applied to companies listed on major stock exchanges. This study aims to determine the traditional and modern analysis of stock performance indicators on the New York Stock Exchange. The company index used was the Dow Jones index. Company performance was measured using two indicators, namely modern performance indicators reflected in Economic Value Added (EVA) and traditional performance indicators reflected in Return on Assets (ROA), Return on Equity (ROE), Earning Per Share (EPS), and Dividend Per Share (DPS). This research was conducted employing purposive sampling on 29 companies indexed by Dow Jones during the 2015-2018 period. The data analysis techniques used were descriptive statistics, classical assumption test, and multiple regression analysis. The results of hypothesis testing in this study show that partially modern performance indicator, namely Economic Value Added (EVA), has an insignificant and negative effect on Stock Return. Meanwhile, traditional performance indicators, namely Return on Assets (ROA), Return on Equity (ROE), Earning Per Share (EPS), and Dividend Per Share (DPS) have a significant and positive effect on Stock Return. The results of simultaneous hypothesis testing show that Economic Value Added (EVA), Return on Assets (ROA), Return on Equity (ROE), Earning Per Share (EPS), and Dividend Per Share (DPS) have a significant and positive effect on Stock Return.Keywords: Economic Value Added (EVA), Return on Asset (ROA), Return on Equity (ROE), Earning Per Share (EPS), and Dividend Per Share (DPS), Stock Return.